The Influence of Financial Ratios on Profit Growth of Property & Real Estate Companies Listed on the IDX for the Period 2019-2021 - Anggun, Nita Putri; Rosyadi, Imron (Almana : Jurnal Manajemen dan Bisnis, 2023)
Profit growth is considered very important for companies because it can be used to predict future business strategies. In addition, profit growth cannot be separated from the company's financial performance as reflected in financial ratios. This research aims to determine and analyze the influence of the current ratio, debt-to-equity ratio, net profit margin, and total asset turnover toward profit growth. The population in this study was 79 property & real estate companies for three years, while the sample was obtained through a purposive sampling method, namely 20 companies. The data analysis technique used in this research is multiple regression analysis using Eviews 9 software. The results showed that partially, CR and NPM had no significant effect on profit growth, while DER and TAT had a significant effect on profit growth. Simultaneously, all independent variables, namely CR, DER, NPM, and TAT affect profit growth. The predictive ability of the four independent variables simultaneously amounted to 33.8%. This shows the predictive ability of financial ratios on profit growth and can influence investors’ investment decisions.